(untitled) (Research, Society and Development, 2022)
This article seeks to analyze the traceability and sustainable use of socio-biodiversity resources as strategic tools for the construction of the new environmental rationality, proposed by Enrique Leff. Through bibliographic research, it was supported by a theoretical foundation based specifically on two works by the author, Environmental Epistemology and Environmental Rationality - social reappropriation of nature. In addition to addressing concepts of traceability and socio-biodiversity, based on other authors, we sought to show how these two categories have the possibility of contributing in a genuine way to the construction of the new environmental rationality presented by Leff. In this way, the theoretical exposition on the theme produced numerous reflections that will contribute to the propagation of the idea of ​​an alternative rationality that makes it possible to reconnect the relationship between man and nature.